GE_GERICHTE P/965/2013 vom 23. Februar 2015 - GE Cour de justice (2015)
PEINE; PEINE PRIVATIVE DE LIBERTÉ; SURSIS À L'EXÉCUTION DE LA PEINE; DÉFENSE D'OFFICE; FRAIS DE LA PROCÉDURE | CP.47; CPP.135.1; RAJ.16